Static compression test of materials - Liu, Chao (Nanyang Technological University, 2021)
Static compression test is one of fundamental experiments to test materials’ properties, such as Yield Strength and Young’s modules. Compression tests are used to evaluate the behavior of a material under applied axial loads and are normally performed using plates or cylindrical shape on compression machine. Through reading and understanding with the American Society for Testing and Materials (ASTM) international standards, in portion the Standard Test Method for Measuring Metallic Materials at Room Temperature (E9-19), follow required dimensions for test specimens and use precise experimental instruments in lab to achieve the accurate results on this project. During this Final Year Project, six medium sized specimens of aluminum alloy 6061-T6 are tested by Shimadzu AGX plus 100kN system. When test specimens are compressed by Shimadzu AGX plus 100 KN machine, both Force-displacement and stress-strain graphs will be obtained from Trapeziumx Software. On the other hand, TDS-303 also record down a group of strain valves from strain gauge. In addition, extract a group of stress value from Trapeziumx Software and strain valves from TDS-303 software, as to combining them together in same Excel file. This method will help to obtain more accurate results from experiment. lastly，compare it with previous researcher’s results and provide some valuable suggestions to improve a more accurate and precious result in future researchers. Throughout this project, I increased Young’s Modulus from 27 GPa to 61.5 GPa compared with past researcher. The percentage difference of literature values for medium sized specimens decreased from 60 % to 10.9%. For Yield Strength, increased Yield Strength value from 270 MPa to 274 MPa, the percentage difference of literature values for medium sized specimens decreased to 2.14%. In summary, both Young’s Modulus and Yield Strength are improved by this experiment. Meanwhile, I have made a great enhancements and modifications on experimental guide for future research.